NUCLEAR ENERGY AS A FUTURE DIRECTION IN SLOVENIA - Špiler, Jože; Bergant, Robert; Žagar, Tomaž (Journal of Energy Technology, 2024)
Based on a recently completed energy/electricity forecast, Slovenia will need new electricity generation capacities. In order to ensure sustainable development for the national economy, bearing in mindenvironmental constraints (Kyoto Protocol), the EU energy and climate package, and the reliable and safe supply of electricity, the nuclear option seems to be the most plausible one tomatch all mentioned requirements. Furthermore, the Slovenian Ministry of the Economy is preparing the National Energy Program (NEP) in which the nuclear energy is recognized as one of the possible options for future development. In recent years, the supply of electricity in Slovenia has been under high demand, due to two main factors. The first is the lack of investment initiatives in new electricity generation capacity.The second is the growth of the gross domestic product (GDP) in Slovenia and consequent increase of the domestic electricity consumption. This situation changed slightly in 2008 with the onset of the current economic crisis, which led to less demand for the electricity. However, this situation must not be used as an excuse to do nothing. It is obvious that the lack of electricity will be only postponed for some years.GEN energija started with the project of new nuclear power plant in the beginning of 2006 and has completed the pre-preparation phase. Many studies and analysis were performed during this initial phase, and all results confirm good harmony with the philosophy of sustainable development, in which ecological, economical and social effects of the project have to be balanced. The studies covered four main areas: analysis of development possibilities in the field of electricity supply in Slovenia, environmental impacts of different technologies, technology itself as well as economic and financial effects of the new nuclear power plant (NPP). All studies were performed by well-regarded foreign and Slovenian institutions, research organisations and companies. The main conclusions based on these studies confirm the justification and technicalfeasibility of the project. The planning of such major projects is of the greatest significance, especially for a new NPP. Therefore, the licensing process with main players is also described and depicted.
Keywords: nuclear power plant; electricity production; electricity consumption; technology; economy; environment; licensing